Unmanned Underwater Vehicles in Crime Detection and Prevention - Zhantureyev, Zhandos; Kassenova, Samal; Baizhanov, Yerbol (Transactions on Maritime Science, 2024)
The relevance of the research is determined by the need to develop effective methods and strategies for the use of modern technologies to ensure the security of marine and underwater facilities in the face of the growing threat of underwater activity, terrorism, and violations of laws at sea. The research aims to analyse and document specific tactical and organisational approaches to the use of unmanned underwater vehicles aimed at increasing the effectiveness of actions related to the detection, investigation, and prevention of underwater crime. Classification, analytical, functional, statistical, and synthesis methods are among the methods used. The research results highlight the global experience of using drones in forensic practice and may serve as a basis for further improvement of legislation in this area. The application of uninhabited underwater vehicles by law enforcement and state bodies in the investigation of criminal offences is considered in the article, and the norms of criminal procedural legislation of the Republic of Kazakhstan regulating the use of technical means in criminal proceedings are analysed. The study reveals the lack of comprehensive research on the use of unmanned underwater vehicles as scientific and technical means for the investigation of certain types of criminal cases, such as drug-trafficking and poaching, and offers recommendations on their use to identify and search for evidence in the aquatic environment. This research has a practical value by providing new methodologies and strategies for organisations and law-enforcement agencies in the field of underwater security, contributing to more effective detection, investigation, and prevention of crime in the maritime and underwater domains.